Formation of logistical costs at dairy enterprises: bibliometric analysis (Journal of Economic Research & Business Administration, 2024)
The article discusses the formation of logistical costs in the dairy industry using bibliometric analysis. The main attention is paid to the research of scientific works and modern techniques aimed at optimizing costs and increasing the economic efficiency of logistics processes in the context of the specifics of the dairy industry. Bibliometric analysis allows us to identify key research areas, trends and gaps in the study of logistics costs, as well as to assess the contribution of various authors and organizations to the development of this field. The conducted research revealed the insufficient representation of scientific publications on the topic of logistics costs in the dairy industry in the international Scopus database over the past five years, which confirms the relevance of this study.The purpose of the article is to identify the main areas of activity of researchers in the academic environment, providing quantitative research data on the mechanism of formation of logistical costs based on bibliographic analysis and evaluation of research sources.The scientific research highlights the need to use modern analytical approaches to better understand the cost structure and develop effective management solutions that will reduce costs and increase the competitiveness of dairy enterprises. The results of the bibliometric analysis make it possible to identify the main authors and study the proposed methodology, which is especially useful for managers, economists and researchers involved in logistics processes in the agro-industrial sector.Special attention is paid to the methodology of bibliometric analysis, which made it possible to identify key trends, gaps and promising areas in the study of logistics costs. The results of the analysis are focused on solving practical tasks of the dairy industry, including optimizing the transportation, storage and distribution of dairy products. The data obtained became the basis for the development of effective strategies for managing logistics processes that help reduce costs and increase the competitiveness of dairy enterprises.For research in bibliometric analysis, the main task of the research will be data processing and analysis using the capabilities of special programs and devices such as Vosviewer based on data from modern bibliographic databases SCOPUS, Web of Science, Mendeley.Key words: logistics, logistical costs, bibliometric analysis, cost optimization, dairy industry.